2019
DOI: 10.1007/s13202-019-0707-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of foam stability at varying salinities and surfactant concentrations using bulk foam tests and sandpack flooding

Abstract: Two conventional approaches for foam screening are core/sandpack flooding and bulk foam stability tests. The former is more accurate, but requires expensive equipment and long test duration. For initial screening, the faster and cost-effective bulk foam stability tests are used to narrow down the selection to a few surfactants, which are then further tested using corefloods/sandpacks. The bulk foam stability tests have been historically used for surfactant selection at a fixed salinity and fixed surfactant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Increase in foam stability due to a decrease in the foam collapse rate in saline surfactant solutions has been shown in experimental studies using bubble columns, but the bubbles size and initial foam volume decrease (Varade and Ghosh 2017;Behera et al 2014;Nasr et al 2020). For each type of surfactant solution, there is a limiting salinity, above which the lamellas rupture.…”
Section: Impact Of Salinity On Foamability and Foam Stabilitymentioning
confidence: 89%
“…Increase in foam stability due to a decrease in the foam collapse rate in saline surfactant solutions has been shown in experimental studies using bubble columns, but the bubbles size and initial foam volume decrease (Varade and Ghosh 2017;Behera et al 2014;Nasr et al 2020). For each type of surfactant solution, there is a limiting salinity, above which the lamellas rupture.…”
Section: Impact Of Salinity On Foamability and Foam Stabilitymentioning
confidence: 89%
“…They found that as the temperature increased, the foam quality factor decreased, indicating reduced foam stability. Nagar Nadia Nasr et al [110] conducted a comparative study on foam stability, investigating the impact of salinity and surfactant concentrations through bulk foam tests and sandpack flooding. They used the mixed anionic and amphoteric surfactant MFOMAX with pure nitrogen.…”
Section: Value Of L E S Foam Stability To Oilmentioning
confidence: 99%
“…37 Figure 17 shows that with the increase of salinity, the liquid carrying rate of UT-6 gradually decreased, and when the salinity increased to 80 000 mg/L, the liquid carrying rate of UT-6 could still reach 70.2%, indicating that UT-6 had the liquid carrying capacity to meet the production requirements when the salinity was 80 000 mg/L. 38 3.6. Surface Tension Reduction Capacity.…”
Section: Dynamic Liquid Carrying Capacitymentioning
confidence: 99%